Ancaman Kerapuhan Struktural Industri Pengolahan Di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRAK Industrial process in Indonesia, up to now, produces a dual performance. It is relatively high growth has not yet succeeded to release some structural problems. Four causes can be argued to point out its reasons. Those are the increasing industrial concentration, the weak of industrial linkage, highly protective structure, and inefficiency. Test by some measures have undoubtedly proved our analysis. This article attempt to describe briefly a number of weaknesses sector which could weaken the manufacturing structure in Indonesia and propose some measures that would improve the current structure. Significant transformation seems prevail limitedly in large-and-medium scale industries. It does not, however, hold for small and handicraft ones. Large-scale industries have been an engine motoring growth of manufacturing sector and the whole economy as well. However, they too have been widening sector and spatial gaps in the country. Since equality is as important as growth in our development, it is reasonable to question their motoring role. One may call them a "leaving" rather than a "leading" engine. Keywords: equality, manufacturing sector